2020
DOI: 10.1007/s00167-020-05861-5
|View full text |Cite
|
Sign up to set email alerts
|

Most unicompartmental knee replacement revisions could be avoided: a radiographic evaluation of revised Oxford knees in the National Joint Registry

Abstract: Purpose The purpose of this study was to understand why the revision rate of unicompartmental knee replacement (UKR) in the National Joint Registry (NJR) is so high. Using radiographs, the appropriateness of patient selection for primary surgery, surgical technique, and indications for revision were determined. In addition, the alignment of the radiographs was assessed. Methods Oxford UKR registered with the NJR between 2006 and 2010 and subsequently revised were identified by the NJR. A blinded review was und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 36 publications
3
38
1
1
Order By: Relevance
“…First, it is a retrospective study of a consecutive case series and there was not a comparative group. Nevertheless, the signi cant low incidence of PPOP after arthroplasty incorporating elimination of MAP in this series compared to other reports [1]- [9] still provides evidence to our hypothesis that MAS is a cause of PPOP. Second, as this is a case series by a single surgeon who utilized the same surgical technique in every case, we are unable to assess other factors such as the approaches and the extent of fat pad resection which might associated with PPOP after arthroplasty.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…First, it is a retrospective study of a consecutive case series and there was not a comparative group. Nevertheless, the signi cant low incidence of PPOP after arthroplasty incorporating elimination of MAP in this series compared to other reports [1]- [9] still provides evidence to our hypothesis that MAS is a cause of PPOP. Second, as this is a case series by a single surgeon who utilized the same surgical technique in every case, we are unable to assess other factors such as the approaches and the extent of fat pad resection which might associated with PPOP after arthroplasty.…”
Section: Resultssupporting
confidence: 54%
“…No evidence of loosening or wearing of the prostheses was found by radiographic examinations in all groups. [5], [18] and is also a common postoperative complaint after UKA [6]- [9]. According to the ndings of this study, the elimination of MAP during either TKA or UKA could avoid unknown causes of PPOP during more than 3 years follow-up.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The Knee Society scores and all subscales of KOOS were statistically improved in all groups (Tables 3 and 4). [5], [18] and is also a common post operative complaint after UKA [6]- [9]. According to the ndings of this study, the elimination of MAP during either TKA or UKA could avoid unknown causes of PPOP during more than 3 years follow-up.…”
Section: Resultsmentioning
confidence: 71%
“…However, persistent postoperative pain (PPOP) has been a common occurrence in about 10-53% of patients after a total knee arthroplasty (TKA) and is associated with reduced health-related quality of life [1]- [5]. Studies regarding unicompartmental knee arthroplasties (UKAs) also reported a high incidence of medial knee discomfort and pain which did not correlate with the postoperative radiographic scores, preoperative arthritis, and the positioning of the prosthesis and might lead to unnecessary revisions [6]- [9]. Many factors may be responsible for a painful knee prosthesis.…”
Section: Introductionmentioning
confidence: 99%